IMPLIKASI PELATIHAN PENGUATAN KAPASITAS KELOMPOK DALAM MENGEMBANGKAN KEMANDIRIAN USAHA - Suwardi, Surachman (Jurnal Ilmu-Ilmu Pertanian, 2011)
The objectives of this evaluation were to analyze the influence partially and simultaneously of capacity building activities by Field Extension Workers (FEWPP), Field Liason Officers (FLO/PMT)' aid partipation of Farmers Group Assosiation (Gapoktan) on adoption level on group capacity building program. The evaluation object was a Farmer's Group Assosiation guided through Rural Agribussines Development Program (RADP/PUAP) in 14/est Java and Central Java Provinces using obserttation and interview methods. The respondents were 184 farmers chosen by the clusters sampling and disproportionate random sampling. The study was carried out during I months on August 2011. The data were collected descriptively and verificatively analyzed using the Structure Equation Modeling. The results of this evaluation indicated that the first is capacity bulding learning by Agricultural Extension Workers , Field Liason Officers, and member's partisipation of Farmer's Group Assosiation influenced significantly partially and simultaneously on adoption level of Farmer's Group Assosiation on capacity building program; the second is need q reorientation Capacity Building Training.